2010
DOI: 10.1308/003588410x12699663905078
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of radiologically-guided steroid injections for trapeziometacarpal osteoarthritis

Abstract: All patients with TMJ osteoarthritis who were given an intra-articular injection of steroid (40 mg Triamcinolone) and local anaesthetic (either 1% Lidocaine or 0.5% Bupivicaine) in our out-patient clinic were considered for inclusion in the audit. The clinical decision to offer a patient an injection was completely independent of this audit. The Conservative treatments include intra-articular steroid injections. PATIENTS AND METHODS This clinical, observational study prospectively reviewed the longevity of ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 11 publications
1
30
0
2
Order By: Relevance
“…20 Within balneotherapy, the use of sulphurous spa water alone was shown to be more effective than that of warm tap water exclusively in the reduction of pain in patients with hand OA. 21 Another Radial nerve mobilization 10,11 Arnica gel 30 Metacarpal osteotomy 45 Maitland's passive accessory mobilization 12 Topical analgesic + paraffin bath therapy 31 Carpometacarpal arthrodesis 45 Joint mobilization + neural mobilization + exercise 13 Intraarticular corticosteroid injections [32][33][34][35] Joint replacement 45 Custom-made splinting 17,18 Intraarticular hyaluronic acid injections 36 single-blind RCT showed that paraffin bath therapy in patients with bilateral hand OA was successful in reducing stiffness and pain at rest and during activities of daily living. As well, range of motion was enhanced in one hand, and muscle strength was better maintained as compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Within balneotherapy, the use of sulphurous spa water alone was shown to be more effective than that of warm tap water exclusively in the reduction of pain in patients with hand OA. 21 Another Radial nerve mobilization 10,11 Arnica gel 30 Metacarpal osteotomy 45 Maitland's passive accessory mobilization 12 Topical analgesic + paraffin bath therapy 31 Carpometacarpal arthrodesis 45 Joint mobilization + neural mobilization + exercise 13 Intraarticular corticosteroid injections [32][33][34][35] Joint replacement 45 Custom-made splinting 17,18 Intraarticular hyaluronic acid injections 36 single-blind RCT showed that paraffin bath therapy in patients with bilateral hand OA was successful in reducing stiffness and pain at rest and during activities of daily living. As well, range of motion was enhanced in one hand, and muscle strength was better maintained as compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of the injection was not related to OA severity, and patients with previous injections had reduced duration of benefit. 32 A similar review determined that from a total of 41 patients undergoing a single injection, 76% reported pain relief lasting an average of four weeks. 76% continued to have pain after a median follow-up of three years, yet 59% were satisfied with the outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of corticosteroid injections is widely debated with several studies demonstrating conflicting conclusions. (Day, Gelberman et al 2004;Meenagh, Patton et al 2004;Khan, Waseem et al 2009;Swindells, Logan et al 2010) A combination of these two treatments has shown to be effective in stage I and stage II disease. (Swigart, Eaton et al 1999 Surgical treatment should be considered when conservative measures have failed to relieve pain and improve day to day thumb function.…”
Section: Osteoarthritis Of the Carpometacarpal Jointmentioning
confidence: 99%
“…It is believed that silicone cannot withstand the same amount of compressive forces as bone and therefore prone to fragmentation and development of silicone synovitis. (Swindells, Logan et al 2010) As a result, different implants such as pyrocarbon and degradable polyurethanurea spacers have been used. Pyrocarbon implants have elastic properties similar to cortical bone and therefore may allow for better transfer of stress load.…”
Section: Osteoarthritis Of the Scaphotrapeziotrapezoid Jointmentioning
confidence: 99%